A Christian-Based Counseling Model in Education: A Conceptual Framework - Amanatidis, Nikolaos (Journal of Education and Religious Studies, 2026)
This article explores the integration of counselling within educational frameworks through the lens of Christian pedagogy and edification, focusing on its role in the holistic development of educators and students in Eastern Thessaloniki, Greece. The study aims to outline how Christian values can be effectively integrated into counselling practices to address personal, pedagogic, and social challenges such as bullying and interpersonal conflicts encountered in modern school reality. Utilizing a research methodology that synthesizes existing literature with Christian pedagogical strategies, the study proposes the "Christian-Based Counselling Model". Results indicate that incorporating values like kindness, compassion, and forgiveness fosters a supportive environment for effective decision-making. Key findings highlight the effectiveness of structured steps, including active listening, the use of biblical narratives for spiritual guidance, and the creation of "quiet spaces" for reflection. These practices, along with communal activities such as thematic clubs and educational visits, reinforce a sense of belonging and ethical growth. The implications suggest that this synergistic approach provides a robust framework for navigating spiritual crises and professional obstacles, ultimately empowering members of the school community to become ethically sensitive and resilient participants in contemporary society.